Poplar Biochar as an Alternative Substrate for Curly Endive Cultivated in a Soilless System - Leo Sabatino; Giovanni Iapichino; Rosario Paolo Mauro; Beppe Benedetto Consentino; Claudio De Pasquale (Applied Sciences, 2020)
Imminent necessity for eco-friendly and low-cost substitutes to peat is a defiance in the soilless plant cultivation systems. Wood biochar could entirely or partly substitute peat as a plant growing constituent to produce vegetables. Nevertheless, knowledge concerning potential plant performance of leafy green vegetables grown on wood biochar is restricted. The present study assessed the main physicochemical traits of various growing media constituted by decreasing the content of peat and by increasing the percentages of poplar wood biochar. Yield, nutritional and functional properties of curly endive plants cultivated in a protected environment were also tested. Biochar was pyrolyzed from poplar (Populus nigra L.) at 450 or 700 °C for 48 h. Increasing biochar concentration and pyrolysis temperature resulted in higher pH, EC and K content of the growing mediums. Biochar was also effective in increasing particle density and bulk density. Biochar at 70% and pyrolysis temperature of 450 °C significantly increased head fresh weight by 47.4%, head height by 24.9%, stem diameter by 21.5% and number of leaves by 80.8%, respectively compared with the control (100% peat). Head dry matter content, root dry matter content, SSC, ascorbic acid and total phenolic were also significantly affected by this treatment. Furthermore, the addition of biochar and the use of higher pyrolysis temperature decreased N leaves concentration. This represents a particularly important target for leafy green vegetables healthiness.